2010
DOI: 10.1021/np100044t
|View full text |Cite
|
Sign up to set email alerts
|

Lactonecembranoids from Croton laevigatus

Abstract: Six new cembranoids, laevigatlactones A-F (1-6), and the known compound neocrotocembraneic acid (7) were isolated from leaves of Croton laevigatus. Their structures were elucidated on the basis of spectroscopic analysis, and that of 1 was confirmed by X-ray crystallography. Compound 2 exhibited modest cytotoxicity against HeLa cells, with an IC(50) value of 38.4 microM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0
2

Year Published

2011
2011
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 10 publications
0
25
0
2
Order By: Relevance
“…The 1 H-1 H COSY experiment showed connectivity of three moieties: I: 1 CH 2 -2 CH 2 -3 CH 2 ; II: 5 CH-6 CH 2 -7 CH 2 ; and III: 9 CH-11 CH(O)-12 CH 2 . The HMBC correlations from CH 3 -19 (d H 0.79, 3H, s) to C-3 (d C 35.1), C-5 (d C 44.4), and C- 18 (d C 15.7); from H [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]each 1H,d,J ¼ 11.2 Hz) to C-3, C-5, and C-19 (d C 17.7); and from H 2 -2 (d H 1.50 and 1.60, each 1H, m) to C-4 (d C 37.5) indicated that C-4 connected units I and II together. The HMBC correlations from CH 3 -20 (d H 0.96, 3H, s) to C-1 (d C 41.4), C-5, and C-9 (d C 66.0) and from H 2 -1b (d H 0.96, 1H, m) to C-9 suggested that C-10 (d C 35.9) connected units I and III together.…”
Section: Resultsmentioning
confidence: 99%
“…The 1 H-1 H COSY experiment showed connectivity of three moieties: I: 1 CH 2 -2 CH 2 -3 CH 2 ; II: 5 CH-6 CH 2 -7 CH 2 ; and III: 9 CH-11 CH(O)-12 CH 2 . The HMBC correlations from CH 3 -19 (d H 0.79, 3H, s) to C-3 (d C 35.1), C-5 (d C 44.4), and C- 18 (d C 15.7); from H [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]each 1H,d,J ¼ 11.2 Hz) to C-3, C-5, and C-19 (d C 17.7); and from H 2 -2 (d H 1.50 and 1.60, each 1H, m) to C-4 (d C 37.5) indicated that C-4 connected units I and II together. The HMBC correlations from CH 3 -20 (d H 0.96, 3H, s) to C-1 (d C 41.4), C-5, and C-9 (d C 66.0) and from H 2 -1b (d H 0.96, 1H, m) to C-9 suggested that C-10 (d C 35.9) connected units I and III together.…”
Section: Resultsmentioning
confidence: 99%
“…Chandonanthus hirtellus 107-111 [38][39][40] Echinodorus macrophyllus 444, 445 [129] Anisomeles indica 342-348 [106][107][108] Cleome spinosa 166-170 [64] Echinodorus grandiflorus 68 [32] Croton gratissimus 638 [182] Croton laevigatus 400-405 [120] Croton oblongifolius 103-105, 520, 554-556 [35,36,157] Greek tobacco 69-102 [33,34] very abundant in tropical reef environments. The abundance and ease of collection of these invertebrates has facilitated an extensive investigation of their secondary metabolism.…”
Section: ] Liverwortmentioning
confidence: 99%
“…The roots and leaves of C. laevigatus have been commonly used as a folk medicine by the Dai people for the treatment of injury from fall and fracture, malaria, and stomachache [1]. As part of our ongoing investigation into Dai medicines from the Croton genera [2,3], a new diterpene (1) (Fig. 1) with trans-clerodane-type structure was isolated from the leaves of C. laevigatus Vahl.…”
Section: Introductionmentioning
confidence: 99%